Nanoparticles Mimicking Viral Cell Recognition Strategies Are Superior Transporters into Mesangial Cells. Issue 11 (22nd April 2020) - Maslanka Figueroa, Sara; Fleischmann, Daniel; Beck, Sebastian; Tauber, Philipp; Witzgall, Ralph; Schweda, Frank; Goepferich, Achim
Abstract: Poor drug availability in the tissue of interest is a frequent cause of therapy failure. While nanotechnology has developed a plethora of nanocarriers for drug transport, their ability to unequivocally identify cells of interest remains moderate. Viruses are the ideal nanosized carriers as they are able to address their embedded nucleic acids with high specificity to their host cells. Here, it is reported that particles endowed with a virus‐like ability to identify cells by three consecutive checks have a superior ability to recognize mesangial cells (MCs) in vivo compared to conventional nanoparticles. Mimicking the initial viral attachment followed by a stepwise target cell recognition process leads to a 5‐ to 15‐fold higher accumulation in the kidney mesangium and extensive cell uptake compared to particles lacking one or both of the viral traits. These results highlight the relevance that the viral cell identification process has on specificity and its application on the targeting strategies of nanomaterials. More so, these findings pave the way for transporting drugs into the mesangium, a tissue that is pivotal in the development of diabetic nephropathy and for which currently no efficient pharmacotherapy exists. Abstract : Nanoparticles (NPs) endowed with viral targeting strategies are presented. A triple‐check for cell identity is implemented by mimicking the initial viral cell attachment, followed by a stepwise enzyme‐activated recognition and internalization. Particles with these viral attributes are able to accumulate in mesangial cells, a therapeutic target of paramount importance due to their involvement in kidney diseases, such as diabetic nephropathy.